Design of cyclic and d‐amino acids containing peptidomimetics for inhibition of protein‐protein interactions of HER2‐HER3. (13th February 2018) - Pallerla, Sandeep; Naik, Himgauri; Singh, Sitanshu; Gauthier, Ted; Sable, Rushikesh; Jois, Seetharama D.
Abstract : HER2 receptors are surface proteins belonging to the epidermal growth factor family of receptors. Their numbers are elevated in breast, lung, and ovarian cancers. HER2‐positive cancers are aggressive, have higher mortality rate, and have a poor prognosis. We have designed peptidomimetics that bind to HER2 and block the HER2‐mediated dimerization of epidermal growth factor family of receptors. Among these, a symmetrical cyclic peptidomimetic (compound18 ) exhibited antiproliferative activity in HER2‐overexpressing lung cancer cell lines with IC50 values in the nanomolar concentration range. To improve the stability of the peptidomimetic, d ‐amino acids were introduced into the peptidomimetic, and several analogs of compound18 were designed. Among the analogs of compound18, compound32, a cyclic, d ‐amino acid‐containing peptidomimetic, was found to have an IC50 value in the nanomolar range in HER2‐overexpressing cancer cell lines. The antiproliferative activity of compound32 was also measured by using a 3D cell culture model that mimics the in vivo conditions. The binding of compound32 to the HER2 protein was studied by surface plasmon resonance. In vitro stability studies indicated that compound32 was stable in serum for 48 hours and intact peptide was detectable in vivo for 12 hours. Results from our studies indicated that 1 of thed ‐amino acid analogs of18, compound32, binds to the HER2 extracellular domain, inhibiting the phosphorylation of kinase of HER2. Abstract : Cyclic peptidomimetics with D‐amino acids were were designed. Compound 32, a cyclic, D‐amino acid‐containing peptidomimetic, was found to have an IC50 value in the lower micromolar range in HER2‐overexpressing cancer cell lines.